Model Capacity Building Pada Pesantren Perbatasan Binaan Dinas Pendidikan Dayah Provinsi Aceh - Muhammad Anggung Manumanoso Prasetyo; Bashori Bashori; Masriani Masriani (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2020)
The era of globalization demands education institution to be adaptive, creative, and innovative, including Islamic boarding schools as the institutions of Islamic education which become the national cultural heritage. One of the innovative programs is capacity building as a series of strategies aimed at increasing efficiency, effectiveness, and responsiveness of performance. This study was directed to explore capacity building implementation at Darul Amin Islamic modern boarding school Southeast Aceh. A qualitative research approach with a case study as the research strategy was implemented. The results of the study showed that capacity building focused on three dimensions, namely (1) human resource development; (2) organizational strengthening, and (3) institutional reform. The principle of Darul Amin capacity building contained the elements of participation, repetition, relevance, transfer, and feedback. In the process of capacity building, there were four stages, namely (1) pre-formal stage (pilot education organization); (2) formal stage (potential education organization); (3) transitional stage (national standard education organization); and (4) autonomous stage (international standard education organization). Towards the existence of the institution, Darul Amin also made various efforts at various levels, namely the system level, organizational level, and individual level.